A comparison between Malay and American responses to compliments in English - Md Ngadiran, Nurizah (2009)
This investigation is pertaining to a comparison of compliment responses between Malay and American responses to compliments in English. The respondents of this research comprise of 10 Malays and 10 Americans; half of them are males and another half of the respondents are females, aged between 20 to 22 years old and currently, they are studying in a tertiary level. In the process of achieving the objectives of the study, the instruments used in this research were a set of Discourse Completion Test (DCT) and a number of interview questions. The findings suggest that there are a few similarities as well as differences of compliment responses produced by the Malay and the American respondents involved in this research. Moreover, the compliment response patterns produced by the two groups of respondents based on their gender have managed to be discovered in this investigation. Last but not least, this paper has also highlighted the underlying reasons for the choices of compliment responses produced by the respondents in the DCTs distributed to them earlier on which include social factors, the influence form mass-media, subject matters being complimented on, as well as their own belief.